Motivational Determinants of Accounting Students’ Engagement in Tax Brevet Programs: Insights from a Behavioral Intention Framework - Yudea; Dika Karlinda Sari; Selviana (P3M Politeknik Negeri Banjarmasin, 2025)
This study aims to analyze the influence of tax knowledge motivation, career motivation, and economic motivation on accounting students' interest in pursuing tax brevet certification, grounded in the Theory of Planned Behavior. Utilizing an explanatory quantitative approach, data was collected hybridly (147 face-to-face respondents and 129 online respondents) via structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling. The results confirm a significant positive influence of all three motivational factors, with tax knowledge motivation emerging as the strongest predictor, followed by career motivation and economic motivation. The findings indicate that students motivated to deepen their tax competency, enhance career prospects, and achieve financial stability are more inclined to pursue the program. However, a gap between high motivation and intention realization was identified, potentially attributed to financial constraints, time limitations, or insufficient institutional support. Consequently, educational institutions need to align academic programs with labor market demands and address implementation barriers to bridge the motivation-behavior gap in career-oriented education.